KESINONIMAN DALAM BAHASA INDONESIA - E Zaenal Arifin (Universitas Nasional, 2015)
Reviews of synonymy in Indonesian is aimed to describe the various issues related to equality of words in our national language. The method used is qualitative descriptive method. The theoretical framework of this review is based on the opinion of D.A. Cruse in Lexical Semantics, and other Semantics expert opinion. Retrieved complex description of synonymy in this language, i.e. absolute synonym, cognitive synonym, plesionym, partial synonym, and congruous synonym. Synonyms are used so there are variations that sentence constructed by the words will be able to make it live and concrete the use of one’s language so that the communication between speachers will be more attractive.